2022
DOI: 10.1111/jdi.13793
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive sleep apnea, prediabetes and progression of type 2 diabetes: A systematic review and meta‐analysis

Abstract: Aims/Introduction: Obstructive sleep apnea (OSA) is related to prediabetes and diabetes. Whether patients with OSA have a higher risk of prediabetes/diabetes remains unclear. We aimed to carry out a meta-analysis of published studies to evaluate the relationships between OSA and prediabetes and diabetes, and the impact of the severity of OSA on diabetes. Materials and Methods: The PubMed, EMBASE and Cochrane databases were searched from January 2011 to July 2021. The associations between OSA and impaired fasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…Moreover, OSA and depression have common risk factors associated with cardiovascular disease and metabolic syndrome [ 6 , 10 ]. The frequency of comorbidities in our study was represented by essential hypertension (63%), ischemic heart disease (28%), and diabetes mellitus (22%), as this result supports the previous argument.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, OSA and depression have common risk factors associated with cardiovascular disease and metabolic syndrome [ 6 , 10 ]. The frequency of comorbidities in our study was represented by essential hypertension (63%), ischemic heart disease (28%), and diabetes mellitus (22%), as this result supports the previous argument.…”
Section: Discussionmentioning
confidence: 99%
“…Studies showed that the prevalence of moderate-to-severe sleep-disorder breathing in adults is 23.4% in women and 49.7% in men [ 4 ]. OSA is an independent risk factor for cardiovascular diseases, essential hypertension [ 5 , 6 ], coronary artery disease, stroke, cerebrovascular disease [ 7 , 8 ], metabolic syndrome [ 9 ], and diabetes [ 10 ]. Sleep fragmentation, hypoxia, and persistent sleep loss lead to symptoms, such as depression since the frontal lobe centers responsible for emotions are sensitive to poor quality sleep [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the hypothesis models proposed by the current study rely on a cross-sectional design, and no longitudinal data were available. Given that the causal relationships between sleep apnea, BMI, and type 2 diabetes are likely dynamic [42,43], further long-term longitudinal studies are needed to clarify the dynamic association. Also, because the population-level, rather than individual-level data, were used in our study, whether BMI is the effect modifier in the associations of sleep apnea and type 2 diabetes was not tested.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Surgery and CPAP treatment break the patterns of sleepiness and desaturation [43], avoid the release of catecholamines, and prevent insulin resistance syndrome and damage to the autonomic system. These treatments also help to limit or prevent the consequences of obesity and metabolic syndrome inherent in diabetes type 2 [44][45][46][47].Fig. 4 This study has some study limitations.…”
Section: Discussionmentioning
confidence: 99%
“…UAS and CPAP can prevent the development of newonset diabetes in patients with OSA [43][44][45][46][47]. Both treatments decreased the incidence of diabetes in OSA patients aged more than 18 years and with a follow-up of 5 years.…”
Section: Discussionmentioning
confidence: 99%